Digital Learning in Vocational High Schools Practices: Insights from Teachers' Experiences - Mochamad Kamil Budiarto; Iwan Maulana; Khusnul Khotimah; Indri Yuli Widya Rulanti; Adhitya Amarulloh; Muhammad Yusron Lutfi (Universitas Sebelas Maret, 2026)
The swift advancement of digital technology and Industry 4.0 has heightened the significance of digital learning in vocational education, necessitating the integration of technology into the teaching and learning process inside schools. This study seeks to examine instructors' experiences in the deployment of digital learning and to determine the elements that facilitate and obstruct its execution. A qualitative case study was performed in a vocational high school, involving four teachers and two administrative and infrastructure personnel recruited via purposive sampling. Data were gathered via semi-structured interviews and observations, thereafter processed by theme analysis. Results demonstrate that digital learning is integrated across planning, instruction, and evaluation methodologies. Educators utilize several digital platforms and tools, including accessibility, user-friendliness, and pedagogical suitability. Despite the school's generally sufficient infrastructure, deficiencies in internet connectivity, device availability, and facility use persist as issues. Educators tackle these challenges using adaptive methods such customized instruction, gamification, peer-assisted learning, and the incorporation of AI literacy. The study indicates that the effective application of digital learning relies on the interplay among teacher practices, digital resources, infrastructural support, and teacher adaptability, hence enhancing the contextual comprehension of the digital learning ecosystem in vocational education.